MILP‐based customer‐oriented E‐Fleet charging scheduling platform. Issue 2 (18th March 2021) - Akaber, Parisa; Hughes, Timothy; Sobolev, Sergey
Abstract: Conventional road transport is a significant contributor to greenhouse gas emissions and air pollution. Electric mobile assets (E‐buses, E‐trucks, E‐taxis, and even E‐ferries) are an efficient, low noise, low emission alternative which could—if operated alongside significant renewable energy capacity—help to improve air quality and avoid catastrophic global warming. In this study, a Mixed Integer Linear Programming‐based solution for operating a fleet of E‐mobile assets has been proposed, considering technical and operational characteristics of different fleet elements. It takes into account customer (E‐fleet operator) objectives, such as load balancing and charging cost minimization. Furthermore, the E‐depot charging capacity increase achieved through integrating an energy storage system has been studied and discussed. The results of the optimization have been discussed and reported using a case study (demonstrating peak reduction of up to 50% and total charging reduction of 27%) and the benefits of operating an E‐fleet using the proposed solution have been discussed from economic and technical perspectives.